O sinaes e os coordenadores de cursos de administração do setor privado: implicações de uma política de avaliação - Silva, Roberto Araújo da (2016)
The research analyzes the SINAES (National System of Higher Education Evaluation) and its implications on the coordination of Management courses from the private sector. Highlights the magnitude of this sector in the brazilian higher education and the high enrollment in its offered courses. Includes the guidelines and the operation of the Management course, focusing on the formation and activity of their coordinators. The study aims to analyze the implications of SINAES on the coordination of Management courses in the private sector, with emphasis on the educational evaluation and regulation concepts expressed in the System initial document. The research adopts a qualitative approach, using document analysis and semi-structured interviews with eight Management courses coordinators from cities of a São Paulo metropolitan region, which does not have public institutions that offer this kind of courses. It has as main results the prospect that SINAES, even after the changes over the years, remains, in the statements of the subjects, as an educational process. For them, the System acts as a guide for coordination, as a tool for the organization of the course, working as a guide for lay people in educational management. Remarks that six of the eight respondents are undergraduate on Management, an area that appreciates planning and control. The favorable positioning about the system does not exclude critics to its operation and its excessive rules. However, the consideration that the SINAES expanded their horizons, both in terms of its functions and relations to the understanding of the course as an educational project, exceeds the critics. And that is what is meant as the idea of educational evaluation.